Curiosity and Autonomy as Factors That Promote Personal Growth in the Cross-cultural Transition Process of International Students - Cankaya, Elif Merve; Liew, Jeffrey; Pizarro de Freitas, Clarissa Pinto (Journal of International Students, 2018)
This study explores measures of curiosity and autonomy as two motivation and personality predictors of personal growth initiative (PGI), an indicator of cross-cultural adjustment. The sample comprised 221 international graduate students. Structural equation modeling was utilized to identify the relations among self-perceived language skills, curiosity, autonomy, and PGI. The results indicate that perceived language skills and autonomy promote curiosity, which in turn facilitates PGI. Implications are suggested to facilitate the adaptation of international students.